2014
DOI: 10.1002/ejlt.201400242
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous lipid microspheres loaded with alkylated norcantharidin derivative norcantharimide: Improved stability and prolonged half‐life

Abstract: To facilitate the preparation of lipid microspheres, norcantharimide, a C14 alkyl chain derivative of norcantharidin, was synthesized and its physicochemical properties were investigated. The N-14NCTDA loaded lipid microspheres (N-14NCTDA LMs) were prepared by a high-pressure homogenization method and characterized in terms of size, zeta-potential, encapsulation efficiency and stability. The apparent oil-water partition coefficient of N-14NCTDA (Log P > 2) was considerably enhanced in comparison to NCTD (Log P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Evaluating the results obtained from this study, Cuifang Cai showed that the compound containing N-C 14 H 29 (Figure 17) side group has a longer half-life and higher volume of distribution (Vss) compared to norcantharidin, as a result of the pharmacokinetic study performed by injecting it into rats. The results obtained from this study suggested that the formulation to be prepared with N-C 14 H 29 is a promising alternative with its high encapsulation efficiency, significant physical and chemical stability, and long half-life (Figure 17) [50].…”
Section: Figure 14mentioning
confidence: 90%
“…Evaluating the results obtained from this study, Cuifang Cai showed that the compound containing N-C 14 H 29 (Figure 17) side group has a longer half-life and higher volume of distribution (Vss) compared to norcantharidin, as a result of the pharmacokinetic study performed by injecting it into rats. The results obtained from this study suggested that the formulation to be prepared with N-C 14 H 29 is a promising alternative with its high encapsulation efficiency, significant physical and chemical stability, and long half-life (Figure 17) [50].…”
Section: Figure 14mentioning
confidence: 90%
“…The entrapment efficiency (EE) of SMEs was measured by ultracentrifugation as previously reported, while the EE was calculated from the following equation : EE(%)=Ctotal×VtotalCwater×VwaterCtotal×Vtotal×100 …”
Section: Methodsmentioning
confidence: 99%